The SAGE handbook of feminist theory - Evans, Mary, 1946- (Los Angeles : SAGE reference, 2014)
At no point in history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This is a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Feminist theory